2022
DOI: 10.3390/metabo12060545
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Metabolism as a Diagnostic Tool for Lung Cancer: Systematic Review

Abstract: Lung cancer is the leading cause of cancer-related mortality worldwide, with five-year survival rates varying from 3–62%. Screening aims at early detection, but half of the patients are diagnosed in advanced stages, limiting therapeutic possibilities. Positron emission tomography-computed tomography (PET-CT) is an essential technique in lung cancer detection and staging, with a sensitivity reaching 96%. However, since elevated 18F-fluorodeoxyglucose (18F-FDG) uptake is not cancer-specific, PET-CT often fails t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…Glutamine is the top 3 recorded metabolite, and differentially expressed in more than 10 cancers, e.g., lung cancer, prostate cancer, and breast cancer. Glutamine is reported as an essential metabolite that has been extensively studied in cancer research ( 17 ), and considered as an important biomarker for early cancer diagnosis ( 18 ). Besides, enriching the metabolites of ovarian benign tumor ( 5 ), liver cirrhosis ( 4 ), prostatitis ( 19 ), and benign lung nodules ( 7 ) by the enrichment tool, we find that the most enriched cancer or trait is ovarian cancer ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is the top 3 recorded metabolite, and differentially expressed in more than 10 cancers, e.g., lung cancer, prostate cancer, and breast cancer. Glutamine is reported as an essential metabolite that has been extensively studied in cancer research ( 17 ), and considered as an important biomarker for early cancer diagnosis ( 18 ). Besides, enriching the metabolites of ovarian benign tumor ( 5 ), liver cirrhosis ( 4 ), prostatitis ( 19 ), and benign lung nodules ( 7 ) by the enrichment tool, we find that the most enriched cancer or trait is ovarian cancer ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies highlight that metabolomics in cooperation with artificial intelligence detectors has the potential for the early detection of lung cancer (reviewed by Mariën et al). [29] With the advent of single-cell RNA sequencing (scRNA-seq), early lung cancer was featured with dysregulation of lipid metabolism in a study, and further detection on plasma untargeted lipidomics identified nine lipid-based models that reached more than 90.00% sensitivity and 92.00% specificity in two validation cohorts. [30] In addition, a study on salivary metabolomics identified differential metabolites that can distinguish early lung cancer patients from healthy controls with a sensitivity of 97.2% and a specificity of 92%.…”
Section: Implementation For Early-stage Lung Cancer Diagnosticsmentioning
confidence: 99%
“…In our work, GL and GP constituted 45% and 31% of the total lipid content detected in healthy mice lung samples (Figure 6A). In general terms, the pulmonary surfactant is composed of a mixture of 80% 35,36 . In addition to PC, other phospholipids found in pulmonary surfactants, such as PE, play a crucial role in facilitating and promoting curvature in non-bilayer surfactant forms, which are essential intermediates during the transitions from bilayers to interfacial films and their interconversions throughout surfactant metabolism.…”
Section: Lila Potentiated To Shed Light On the Mice Lung Lipidome Lan...mentioning
confidence: 99%